Skills, Parental Sorting, and Child Inequality - Martin Nybom; Erik Plug; Bas van der Klaauw; Lennart Ziegler (Institute of Labor Economics (IZA), 2022)
This paper formulates a simple skill and education model to explain how better access to higher education leads to stronger assortative mating on skills of parents and more polarized skill and earnings distributions of children. Swedish data show that in the second half of the 20th century more skilled students increasingly enrolled in college and ended up with more skilled partners and more skilled children. Exploiting college expansions, we find that better college access increases both skill sorting in couples and skill and earnings inequality among their children. All findings support the notion that rising earnings inequality is, at least in part, supply driven by rising skill inequality.
Keywords: J62; I24; J12; J11; 330; assortative mating; intergenerational mobility; education; earnings inequality